THE DEVELOPMENT OF STUDENTS ACTIVITY SHEET (SAS) WITH CHEMO-ENTREPRENEURSHIP ORIENTED ON COLLOID MATTER IN 11th GRADE TO TRAIN CREATIVE THINKING SKILLS (UNESA Journal of Chemical Education, 2019)
The aim of the research is to produce Students Activity Sheet (SAS) with Chemo-Entrepreneurship oriented on Colloid matter in 11th Grade to Train Creative Thinking Skills which is feasible to use. The feasibility are reviewed based on validity, practicability, and effectiveness of students worksheet. This research is development research using Research and Development (R&D) design with one group pretest and posttest method which is limited trial test was conducted to 12 students of 12th grade of SMAN 1 Driyorejo Gresik. The instrument used in this research were review sheet, validation sheet, observation of students activity sheet, students responses and creative thinking tests. Validation result of content criteria was 86.67% in the highly valid category and construct validity reviewed from language criteria, presentation criteria and display suitability criteria with percentage 86.67%, 85.92% and 86.67% in the highly valid category. The SAS practicality in the very practice category with positive responses of students on the content criteria was 100%, language criteria was 91.67%, presentation criteria was 94,44%, graphic criteria was 94.44% and its supported by observation result of students activity which declared that the SAS activity 100% was carried out well during the limited trial process. The SAS effectiveness has shown that N-gain score of students get value ≥0,7 which is 83.33% of students in the high category and 16.67% of students in the medium category. Keywords: SAS feasibility, Chemo-Entrepreneurship, Creative Thinking skills, Colloid.